Effects of creatine supplementation on biomarkers of hepatic and renal function in young trained rats - Souza W.M. (2013)
Creatine supplementation has been widely used by athletes and young physical exercise practioneers in order of increasing muscle mass and enhancing athletic performance, but their use/overuse may represent a health risk on hepatic and renal impaired function. In this study, we evaluated the effects of 40 days of oral creatine supplementation on hepatic and renal function biomarkers in a young animal model. Wistar rats (5 weeks old) were divided in five groups (n = 7): control (CONTR), oral creatine supplementation (CREAT), moderate exercise training (EXERC), moderate exercise training plus oral creatine supplementation (EXERC + CREAT) and pathological group (positive control for liver and kidney injury) by the administration of rifampicin (RIFAMPICIN). Exercise groups were submitted to 60 min/day of swimming exercise session with a 4% of body weight workload for six weeks. The EXERC + CREAT showed the higher body weight at the end of the training protocol. The CREAT and EXERC + CREAT group showed an increase in hepatic (Aspartate transaminase and gamma-glutamyl transpeptidase) and renal (urea and creatinine) biomarkers levels (p < 0.05). Our study showed that the oral creatine supplementation promoted hepatic and renal function challenge in young rats submitted to moderate exercise training. © 2013 Informa Healthcare USA, Inc.